Composition of bulbuls (Pycnonotidae) in logged and unlogged forests at Berkelah Forest Reserve, Maran, Pahang - Bing, Diau Ya; Hussin, Mohamed Zakaria (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Logging affects the distribution and abundance of forest food resources that are important to birds. A study on the species composition of bulbuls (Pycnonotidae) was carried out in the Berkelah Forest Reserve, Maran, Pahang. The main objective was to determine the species composition and abundance of bulbuls found in logged and unlogged forests. In the study area, a total of 28 bird species (80 individuals) and 42 species (90 individuals) were captured using the mist-netting method (60 nets) in the unlogged and logged forests, respectively. The results suggest that the bird species composition was higher in the logged compared to the unlogged forest. The diversity analysis showed higher species composition of understorey birds in the logged forest than the unlogged forest. With regards to bulbuls, a total of 43 individuals (12 species) were captured - however more species were found in the logged compared to the unlogged study sites. Environmental factors such as microclimate and the presence of invasive plants may have affected the understorey bird population and species composition.